Association between risk of ischemic stroke and the rs17216473 single nucleotide polymorphism in the 5-lipoxygenase-activating protein gene locus - Pavlenko, O.Yu.; Strokina, I.G.; Drevytska, T.I.; Karvatsky, I.M.; Sokurenko, L.M.; Dosenko, V.E. (Medicni Perspektivi, 2025)
Multiple studies have focused on the genetic basis of stroke, in particular on single nucleotide polymorphisms. However, the contribution of single nucleotide polymorphism rs17216473 in the gene that encodes ALOX5AP to stroke has been researched too little. The purpose of the work is to study the association between the risk of ischemic stroke and the single nucleotide polymorphism rs17216473 of the gene that encodes ALOX5AP, in particular, the G/G and G/A genotypes and alleles A and G, within the Ukrainian population. DNA extracted from leukocytes of venous blood of healthy donors (control group) and patients (stroke group) was studied. The control group consisted of 110 people, including 60 men (54.5%) and 50 women (45.5%), the average age in the group was 58.8±6.2 years, mode (Mo) by group was equal to 64 years. The absence of cardiovascular pathology in the donors was confirmed by anamnesis, electrocardiography and pressure measurement. The stroke group included 109 patients, 58 men (53.2%) and 51 women (46.8%), suffering from an acute violation of cerebral blood circulation (acute ischemic stroke). The focus of brain infarction was localized in the basin of the left middle cerebral artery in 51 patients (46.8%), in the basin of the right middle cerebral artery in 39 (35.8%), in the vertebral-basilar basin in 18 (16.5%) and in the basin of the left anterior cerebral artery in 1 patient (0.9%). 21 of these patients also have a history of ischemic stroke, 15 (13.8%) of them in the same basin and 6 (5.5%) in another vascular basin. The average age of patients at the time of brain infarction was 70.3±10.0 years, mode (Mo) by group was equal to 60 years. In the context of the study of the role of single nucleotide polymorphisms in the occurrence of stroke, the contingent of patients by age and localization of the focus of brain infarction is considered as homogeneous. Healthy donors and stroke patients belonged to the older age group, they are residents of Kyiv, the percentage of men and women in the indicated groups was almost the same, therefore, according to socio-demographic indicators, the group of stroke patients and the control group can be considered homogeneous. Taking into consideration the average age and mode (Mo) in the groups (58.8±6.2 years, Mo was 64 years in the control group and 70.3±10.0 years, Mo was equal to 60 years in the stroke group), the groups are statistically comparable in age. All women in both groups are postmenopausal. Real-time polymerase chain reaction and the analysis to discriminate alleles were used. The statistical analysis was performed using χ2 criteria and by χ2 criteria with Yates correction. We identified two genotypes, G/G and G/A, of the single nucleotide polymorphism rs17216473 of the gene that encodes ALOX5AP. Humans that were homozygotes for the minor allele A (carrying the A/A genotype) were not found in our study. Genotype G/G was the most prevalent in both the control and stroke groups, without significant difference between these groups. The carries of the G/A genotype were not as significantly represented as those of the G/G genotype. Simultaneously, there was no significant difference in the quantity of G/A genotype carries between the control and stroke groups. The distribution of the G allele was not significantly different between the control and stroke groups. The same trend was observed for allele A; its number in the control group was almost identical to that in the stroke group, Neither the G/G nor G/A genotypes were significantly associated with ischemic stroke risk (p>0.05). Neither allele (dominant allele G or minor allele A) of single nucleotide polymorphism rs17216473 were significantly associated with ischemic stroke risk in the Ukrainian population (p>0.05). No contribution of single nucleotide polymorphism rs17216473 (SG13S377) in the gene encoding ALOX5AP to ischemic stroke onset was observed in a Ukrainian population.